1986
DOI: 10.1007/bf00181253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fixed-ratio length on the development of tolerance to decreased responding by l-nantradol

Abstract: Key pecking of pigeons was maintained under either a 100-response or a 300-response fixed-ratio schedule of food presentation, and animals received 0.03 mg/kg/day l-nantradol prior to experimental sessions. Tolerance developed for initial rate decreases under fixed ratio 100 in 10-12 sessions, but tolerance did not develop under fixed ratio 300 for up to 30 sessions. When the fixed ratio was changed from 300 back to 100, tolerance developed in three to four sessions, and when the fixed ratio was changed from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…These data are consistent with those of Nickel and Poling (1990) who arranged a multiple schedule consisting of FR 5, FR 25, and FR 125 components and who also found that the degree of tolerance was greatest in the smaller-value component. These results also are consistent with other reports of differential tolerance development in multiple ratio schedules with various drugs and species (e.g., Branch, 1990;Hoffman et al, 1987;Hughes & Branch, 1991;Smith, 1986bSmith, , 1990. In Nickel and Poling's study, the unit price was unequal across the three FR sizes because the reinforcement amount was held constant while the FR size was increased.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with those of Nickel and Poling (1990) who arranged a multiple schedule consisting of FR 5, FR 25, and FR 125 components and who also found that the degree of tolerance was greatest in the smaller-value component. These results also are consistent with other reports of differential tolerance development in multiple ratio schedules with various drugs and species (e.g., Branch, 1990;Hoffman et al, 1987;Hughes & Branch, 1991;Smith, 1986bSmith, , 1990. In Nickel and Poling's study, the unit price was unequal across the three FR sizes because the reinforcement amount was held constant while the FR size was increased.…”
Section: Discussionsupporting
confidence: 91%
“…Tolerance to the response-ratedecreasing effects of cocaine developed in the smaller-value components (i.e., FR 5 and FR 25), but did not develop, or developed to a lesser extent, in the large-value components (i.e.,FR 50 or FR 125). A similar relation was obtained between FR parameter and degree of tolerance to other drugs (e.g., morphine, (-)-nantradol, and clonidine), with other species (e.g., squirrel monkeys and rats) and when responding was maintained under multiple random-ratio schedules (Branch, 1990;Hughes & Branch, 1991;Nickel & Poling, 1990;Smith, 1986b;.…”
supporting
confidence: 64%
“…The results of the study by Hoffman et al (1987) showed that tolerance did not develop during FR 125 when that schedule occurred in the context of smaller FR Smith's (1986) data support the suggestion that fixedratio size may be a factor in the development of tolerance, not only to cocaine but to other drugs as well .…”
Section: Discussionmentioning
confidence: 62%
“…She also found that discriminability between ratios improved with absolute ratio size. Although Hobson (1975) et al (1986), and, to some degree, Hughes and Branch (1991), and Smith (1986), where tolerance was observed more often and/or to a greater degree during smaller FR schedules. Further research should attempt to specify the conditions that define whether or not the reduction of a particular reinforcement rate by the repeated administration of a drug will result in the development of tolerance to that effect.…”
Section: Discussionmentioning
confidence: 97%
“…That is, clonidine and/-nantradol decreased accuracy under the FCN schedules, with the magnitude of this effect being considerably larger under the FCN 8. Even though the effects of these drugs on schedule-controlled performance have been documented extensively, little is known about their effects on conditional discriminations in pigeons (Tilson et al 1977;McCleary and Leander 1981 ;Katz 1984;Smith 1986). Nevertheless, similar accuracy-decreasing effects for these drugs have been reported in monkeys trained to discriminate the presence and absence of electric-shock (Dykstra 1981) and in rats trained to discriminate different electric-shock intensities (Genovese and Dykstra 1984).…”
Section: Run Lengthmentioning
confidence: 99%